PERBANDINGAN RESPONS ANTARA MAHASISWA LAKI-LAKI DAN PEREMPUAN TERHADAP KUMPULAN CERPEN KITAB KAWIN KARYA LAKSMI PAMUNTJAK: KAJIAN RESEPSI SASTRA - Nirmala, Nirmala; Nensilianti, Nensilianti; Saguni, Suarni Syam (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2025)
The purpose of this study was to examine the comparative responses of male and female students to the short story collection Kitab Kawin using the Hans Robert Jauss literary reception study which focuses on the horizon of expectations and the spirit of the times of readers. The method used in this study is to use a qualitative research type. Questionnaire and interview techniques were used to collect data from male students in the form of responses to the short story Kitab Kawin. The results of the study showed that there were differences in the responses of male and female students in reading the short story Kitab Kawin in terms of the horizon of expectations and the spirit of the times of readers, the suitability of the horizon of expectations and the spirit of the times of female students was the most compared to male students. This happened because several factors influenced the horizon of readers' expectations, namely the reader's experience, the reader's interest in what they read was different, the reader's social environment, life experiences, psychological differences between men and women.